2011
DOI: 10.1093/mp/ssr037
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic HSP90 Cochaperones HOP and FKBP Interact with Freshly Synthesized Chloroplast Preproteins of Arabidopsis

Abstract: Most chloroplast and mitochondrial proteins are synthesized in the cytosol of the plant cell and have to be imported into the organelles post-translationally. Molecular chaperones play an important role in preventing protein aggregation of freshly translated preproteins and assist in maintaining the preproteins in an import competent state. Preproteins can associate with HSP70, HSP90, and 14-3-3 proteins in the cytosol. In this study, we analyzed a large set of wheat germ-translated chloroplast preproteins wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 69 publications
2
72
0
1
Order By: Relevance
“…2). The process of protein import into chloroplasts can be divided into multiple independent steps: navigation through the cytosol (May and Soll, 2000;Qbadou et al, 2006;Li and Chiu, 2010;Fellerer et al, 2011;Lee et al, 2013a), recognition by receptors at the surface of chloroplasts (Becker et al, 2004;Smith et al, 2004;Li and Chiu, 2010), translocation through the outer and inner membranes (Rensink et al, 2000;Kikuchi et al, 2009Kikuchi et al, , 2013Li and Chiu, 2010), and possibly the pulling step by chaperones at the stroma (Chou et al, 2006;Li and Chiu, 2010;Shi and Theg, 2010;Su and Li, 2010;Chotewutmontri et al, 2012;Inoue et al, 2013;Liu et al, 2014). Each of these steps requires one or more specific factors to mediate the import process.…”
Section: Discussionmentioning
confidence: 99%
“…2). The process of protein import into chloroplasts can be divided into multiple independent steps: navigation through the cytosol (May and Soll, 2000;Qbadou et al, 2006;Li and Chiu, 2010;Fellerer et al, 2011;Lee et al, 2013a), recognition by receptors at the surface of chloroplasts (Becker et al, 2004;Smith et al, 2004;Li and Chiu, 2010), translocation through the outer and inner membranes (Rensink et al, 2000;Kikuchi et al, 2009Kikuchi et al, , 2013Li and Chiu, 2010), and possibly the pulling step by chaperones at the stroma (Chou et al, 2006;Li and Chiu, 2010;Shi and Theg, 2010;Su and Li, 2010;Chotewutmontri et al, 2012;Inoue et al, 2013;Liu et al, 2014). Each of these steps requires one or more specific factors to mediate the import process.…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis was performed in the presence of 50% homemade wheat germ lysate for 45 min at 25°C as described (Fellerer et al, 2011). Samples were centrifuged for 10 min at 20,000g at 4°C, and supernatant was added to 15 mL of TALON magnetic beads (Clontech).…”
Section: Phospho-amino Acid Analysismentioning
confidence: 99%
“…Although lack of phosphorylation does not prevent protein import or lead to mistargeting (Nakrieko et al, 2004), it elevates transport rates mediated by a higher affinity to the receptor protein Toc34 (May and Soll, 2000). Analysis of the binding of 14-3-3 to preproteins revealed that this is not restricted to a few exceptions: approximately 25% out of a population of 41 preproteins were found to associate with 14-3-3 (Fellerer et al, 2011). Additionally, dephosphorylation of chloroplast preproteins has likewise been shown to influence protein import, since it is indispensable for efficient transport of preproteins (Waegemann and Soll, 1996).…”
mentioning
confidence: 99%
“…In the wild type, MgProtoIX and Mg-ProtoIX-ME were shown to accumulate transiently when plants were exposed to oxidative stress (Stenbaek et al, 2008;Kindgren et al, 2011;Zhang et al, 2011), and in response to the tetrapyrrole accumulation, the ATPase activity of cytosolic HEAT SHOCK PROTEIN90 (HSP90) proteins is inhibited, which leads to a change in nuclear gene expression (Kindgren et al, 2012). HSP90 is a molecular chaperone that interacts with proteins in their near-native state and is essential for maintaining the activity of signaling proteins (Young et al, 2001) as well as preventing the protein aggregation of freshly translated chloroplast preproteins (Fellerer et al, 2011). HSP90 also has been reported to be required for proper regulation of the circadian clock.…”
mentioning
confidence: 99%